ANALISIS PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PETANI PEMBUDIDAYA LELE DI PEKON LUGUSARI KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - Zhafirah, Aldina Anis; Haryono, Dwi; Nurmayasari, Indah (Indonesian Journal of Socio Economics, 2023)
This research aims to analyze the income of catfish, household income of catfish farmers, and the level of welfare of catfish farmers in the village of Lugusari, Pagelaran sub-district, Pringsewu regency. This research  used a census method and the location was selected purposively in the village of Lugusari, Pagelaran sub-district, Pringsewu district with the consideration that this location is the biggest potential for catfish production. The respondents of this study were catfish farmers, amounting to 59 people. Data were collected from July to August 2020. The analysis used is quantitative analysis to determine the amount of catfish income and household income, as well as qualitative descriptive analysis to determine the level of household welfare.  The results of this study indicate that the average income of catfish farming is IDR 102.932.493 divided into 4 stocking seasons. The household income of farmers is dominated by catfish farming income, which is 84,89 % of the total respondents. The majority of respondents are in the welfare category.